2007
DOI: 10.1007/s12029-007-9004-9
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerous Change Decreases the Accuracy of Endoscopic Ultrasonography Diagnosis for the Invasive Depth of Early Gastric Cancer

Abstract: The accuracy of endoscopic ultrasonography tumor staging was not sufficient for the lesions with ulcerous changes in our study. Therefore, we should be careful to perform endoscopic submucosal dissection for lesions with ulcerous changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 24 publications
5
54
0
1
Order By: Relevance
“…It is important to investigate the invasive depth of the tumor before ESD. However, the accuracy of T staging in EGC with ulcer is very low [14]. Third, the presence of ulceration interferes with complete resection and promotes a long procedure time and high risk of adverse events such as bleeding and perforation [3,[6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to investigate the invasive depth of the tumor before ESD. However, the accuracy of T staging in EGC with ulcer is very low [14]. Third, the presence of ulceration interferes with complete resection and promotes a long procedure time and high risk of adverse events such as bleeding and perforation [3,[6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…This contributes to disease estimation, selection of surgical procedure and prognosis assessment (Willis et al 2000;Kwee and Kwee 2007). With constant improvements in EUS, its superiority in T and N staging of gastric cancer has been demonstrated (Greenberg et al 1994;Hizawa et al 2002;Akashi et al 2006). However, due to the limitation of the probe frequency of endoluminal sonography and the penetration depth of the ultrasonic beam, its inferiority in M staging of gastric cancer (i.e., its incapacity to accurately predict the distant metastasis of gastric cancer) is also shown (Ziegler et al 1993;Bhandari et al 2004;Chen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Choi et al demonstrated that EUS was not superior to white light endoscopy in terms of determining the depth of cancer invasion in patients with suspected EGC (67.4 vs 73.7 %, respectively; n = 955) [27]. At the very least, endoscopists need to recognize that accurate determination of the depth of invasion with EUS could be difficult if the lesion is larger than 5 cm and associated with an ulcer scar [28][29][30].…”
Section: Depth Diagnosis Of Egcmentioning
confidence: 99%